Assessment of Upgrading Strategies to Improve Regional Food Systems in Tanzania: Food Processing, Waste Management and Bioenergy, and Income Generation. (September 2015) - Graef, F.; Schneider, I.; Fasse, A.; Germer, J.U.; Gevorgyan, E.; Haule, F.; Hoffmann, H.; Kahimba, F.C.; Kashaga, L.; Kissoly, L.; Lambert, C.; Lana, M.; et al.
Food security is one of the main goals of rural poor people. To enhance food security in this context, participatory action research can help to ensure sustained success while considering entire food value chains (FVC). This paper assesses the feasibility and potential success of upgrading strategies (UPS) as well as their assessment criteria as developed by German and Tanzanian agricultural scientists. The results form part of a larger participatory research project conducted in two climatically representative regions of Tanzania: semi-arid Dodoma and subhumid Morogoro. This paper presents the findings with respect to food processing, waste management and bioenergy, along with income generation and market participation. Assessments on other components of the FVC, including natural resource management, crop production and consumption, are reported by Graef et al (2015). The assessments for food processing revealed preferences for preservation techniques, oil extraction processes and food storage devices for the semi-arid region. In contrast, in the subhumid region, the experts favoured food storage devices and preservation techniques. Assessments of waste management and bioenergy UPS for both regions indicated the importance of animal feed from crop residues, crop residues as mulch and compost from food waste, although with somewhat different priorities. Assessments on income generation and markets in both regions revealed preferences for savings and credit cooperatives and communication techniques, but also indicated that warehouse receipt systems and guarantee systems had a high impact. Assessments differed between the two different climatic regions, and to some extent also between the nationality of experts and their gender. The authors therefore attach importance to integrating different South–North and female–male awareness in assessments among scientists. Moreover, local and/or regional stakeholders and experts should be involved in developing site-adapted UPS for enhancing FVCs.